Obstetric Violence, Forgotten History of Invisibilized Practices (2018)
Obstetric violence is an issue that is on the agenda worldwide. Every day the struggle of women increases seeking to reduce obstetric violence as a form of violation of the human rights of women and their babies, in order to reduce consequences such as: maternal or neonatal deaths, irreparable damage to health reproductive health of women, psychological damage and traumatisms in the newborn, among many others. The well-being of women in childbirth and the right to give birth in freedom and dignity are sought. That is why the need arises to talk about obstetric violence and review its history to understand the phenomenon and protect the fundamental rights of women and minors in the world.In accordance with the above, this research is proposed, with which it is intended to study the history of obstetric violence, taking a journey from the origins of obstetrics to reach an understanding of the phenomenon in the world. For the development of this research, the analytical and descriptive methods were used, which allowed dividing the global concept, analyzing the historical, social and cultural factors that allowed its birth from obstetric violence, providing a detailed historical profile of the phenomenon.